TINDAK KEJAHATAN INTERNASIONALGENOSIDA RWANDA 1994 - Listi, Anas Tiya; Hadi, Hadi Haerul (LPPM Universitas Bina Bangsa, 2024)
The purpose of this research is as a case study of violations of International Crimes according to Statutaroma, namely the gross human rights crime of Crimes against Humanity (Genocide). Genocide is one of four gross human rights violations within the jurisdiction of the International Criminal Court. Other gross human rights violations are crimes against humanity, war crimes, and crimes of aggression. In the Law of the Republic of Indonesia Article 8 Number 26 of 2000 concerning Human Rights Courts, a gross human rights violation is classified into 2 types, genocide and crimes against humanity. International Crimes are no longer a difficult thing to find, in the current era International Crimes are quite following the times with more and more new cases with different unlawful acts. one of the Genocide Crimes is the 1994 Rwanda Case. The Rwanda case became the world's spotlight because it was the largest Genocide Crime in 1994. Most of the data used through literature studies collected from literature studies, online data searches and documents